2018
DOI: 10.1007/s00330-017-5232-y
|View full text |Cite
|
Sign up to set email alerts
|

Does a combined CT and MRI protocol enhance the diagnostic efficacy of LI-RADS in the categorization of hepatic observations? A prospective comparative study

Abstract: • Hepatic observation may be categorized differently depending on the imaging modality used. • We compared LI-RADS categorization between CT, MRI and combined CT/MRI. • MRI produces higher accuracy and sensitivity, while CT produces higher specificity. • Combining CT and MRI improves LIRADS categorization reports. • Considering additional cost, combined methodology could be restricted to challenging cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 27 publications
2
38
1
Order By: Relevance
“…Our study found a high IRR but a lower sensitivity (30%) than anticipated while maintaining a high IRR. The IRR was consistent with previous studies evaluating the interrater agreement of the LI‐RADS diagnostic categories . After changing the cutoff point for detecting disease to include LR‐TR equivocal, sensitivity remained low (44%) with a decrease in specificity and PPV.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study found a high IRR but a lower sensitivity (30%) than anticipated while maintaining a high IRR. The IRR was consistent with previous studies evaluating the interrater agreement of the LI‐RADS diagnostic categories . After changing the cutoff point for detecting disease to include LR‐TR equivocal, sensitivity remained low (44%) with a decrease in specificity and PPV.…”
Section: Discussionsupporting
confidence: 87%
“…For example, a study looking at 240 patients who underwent MRI surveillance for HCC found the LI‐RADS 4 and 5 criteria to be 86% sensitive and 84% specific at detecting HCC. However, only 12% of the cohort used surgical specimens for the diagnoses, whereas the other 88% used core biopsy or radiologic follow‐up as the referent standard for true HCC . Core needle biopsy has a high false‐negative rate due to the inability to distinguish well‐differentiated HCC from cirrhotic liver and the inaccuracy of targeting specimens .…”
Section: Discussionmentioning
confidence: 99%
“…They observed κ-values for venous thrombus, arterial hyperenhancement, washout appearance, and capsule appearance 0.983, 0.621, 0.546, and 0.549 by CT; 0.991, 0.649, 0.674, and 0.742 by MRI, respectively. They found a good level of reproducibility for all LIRADS classes (κ = 0.895 by CT and 0.926 by MRI) [15].…”
Section: Discussionmentioning
confidence: 95%
“…These are the retrospective nature, the relatively small sample size, and the single-centre design. In some multicentric studies higher reproducibility levels for LI-RADS were found [15,22,23]. Also, all MRI examinations were performed with an extracellular gadolinium contrast agent, and we did not evaluate the liver-specific contrast media.…”
Section: Limitationsmentioning
confidence: 99%
“…Several studies have demonstrated that the LI-RADS categories are discordant between CT and MRI in about 35%-70% of cases [9] . MRI categorizes more benign lesions as LR-1 compared to CT (25%-30% of those lesions were categorized as LR-3 on CT) [11,12] . When excluding the LR-1 category, MRI-assigned categories are higher compared to the CT-assigned categories (12%-31% of LR-5 observations on MRI were categorized as LR-4, 12% as LR-3, and 15%-29% were not seen on CT) [9,11,12] .…”
Section: Ct/mri Diagnostic Algorithmmentioning
confidence: 99%